Location matters: survival of artificial nests is higher in small grassland patches and near the patch edge. (23rd August 2022) - Pretelli, Matías G.; Cavalli, Matilde; Chiaradia, Nicolás M.; Cardoni, Augusto; Isacch, Juan P.
Abstract : Nest survival is an important part of breeding success in grassland ecosystems, and the location of nests can determine vulnerability to different predators. We conducted an experiment with artificial nests to evaluate jointly the predation rate on nests at different spatial scales (landscape, patch and tussock) and the relative abundance of potential nest predators (small mammals and birds) in a temperate grassland area. In November 2014 and 2016, we installed 288 artificial nests in Common Pampas Grass Cortaderia selloana grasslands in the southeastern Pampas region, Argentina. The nests were placed in two 10‐ha plots in a continuous grassland patch (c. 900 ha) within a reserve and in two small grassland patches (1.5 and 1.8 ha) in an agricultural matrix (landscape‐scale), at the patch edge and inside the patches (patch‐scale), and at two heights within the tussock grass (tussock‐scale). In 2016, we also conducted live trapping of small mammals and surveyed birds along strip transects at the sampling sites. Nests located in patches within an agricultural matrix and near the edge had greater relative survival than those set in the reserve and inside the patches, respectively. This might be explained by the lower relative abundance of small mammals that we found outside the reserve. Artificial nest survival values recorded at the landscape‐scale contrasted with those previously observed for natural nests. Our results could be partly explained by differences in nest density between agro‐patches and those within the reserve. Future studies could also evaluate the role of parental nest defence on nest survival.